PENERAPAN MODEL COOPERATIVE SCRIPT UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK SDN TLOGOSARI KULON 01 SEMARANG - Anam, Firda Saiful; Sulianto, Joko; Purnamasari, Veryliana; Raharjo, Susilo (FKIP, PGSD, Universitas Slamet Riyadi, 2024)
The objective of the research is to improve the result of social studies about wawancara of the student class IV SDN Tlogosari Kulon 01 Semarang by implemation model pembelajaran Cooperative Script. The method is used action class that consist of two cycles, each cycles has planning, implementation, observation, and reflection the subject of the research is 28 students. The instrument is used essay test and observation. The result of the research through by implemation model pembelajaran Cooperative Script can improve the students result study, from 28 students, at the beginning the comlpleteness is only 9 students or 33% while 19 students or 67% not complete. The final from 28 students which is not complete is only 4 students or 14% and 24 students or 86% is complete. Keywords: Cooperative Script Learning Model, Learning Outcomes, Indonesian. Â